The economic impact of COVID-19 pandemic on physicians/health care work force in Egypt - Ahmed, Rehab Abdelhai; Salem, Amany Ahmed; Elsebaie, Eman Hany; Shamseldein, Sherif; Hassan, Mustafa Ahmed; Sedrak, Amal Samir (Intelektual Pustaka Media Utama, 2025)
The COVID-19 pandemic has impacted healthcare workers physically, psychologically, and economically. The industry has struggled financially with the cancellation of elective procedures and hesitancy from patients to seek medical help. Thus, this study aimed to assess the economic and work burden of COVID-19 on the health workforce in Egypt. Methods a cross-sectional survey was conducted in Egypt from October 2020 to May 2021. A purposive sample of 763 healthcare workers (HCWs) from Egyptian governorates was included. HCWs were asked to fill out a self-administered questionnaire on Google Forms and printed copies. The questionnaire link was shared on social media forums. Results a total of 763 HCWs responded. Females were 88.2% and more than half were 33 or less years old. Physicians constituted 42.5%, while paramedics 57.5%. The governmental sector represented 61.2%, private sector 14.7% and those who combined both 24.1%. Regarding specialties affected, pediatricians, dermatologists, and nephrologists reported a considerable drop in their regular private work rate, while radiologists were not affected regarding workload or income by the closure. The HCWs acknowledge that COVID-19 has put extreme stress on the healthcare workforce physically, mentally, and financially in a pre-existing challenging environment. The results can help evidence-based decisions by policymakers in Egypt.